2023
DOI: 10.1111/aas.14217
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the haemoglobin level associated with a lower risk of complications after total hip and knee arthroplasty

Abstract: Background: Preoperative anaemia is associated with poor outcomes in surgical patients, but the preoperative haemoglobin cut-off that determines lower morbidity in total knee arthroplasty (TKA) and total hip arthroplasty (THA) is not well established.Methods: Planned secondary analysis of data collected during a multicentre cohort study of patients undergoing THA and TKA in 131 Spanish hospitals during a single 2-month recruitment period. Anaemia was defined as haemoglobin <12 g dl À1 for females and < 13 g dl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(59 reference statements)
2
1
0
Order By: Relevance
“…Our analysis demonstrates that within our machine‐learning risk‐model, the preoperative Hb threshold for an increased risk of prolonged length of stay or readmissions due to medical issues was 14.8 g/dL in both men and women. This is similar as a recent study in about 7000 THA and TKAs (only 25% within fast‐track/ERAS programs) which reported fewer postoperative complications with a Hb >14.0 g/dL 7 . Thus, the results of both studies support removing the gender‐specific Hb criteria for preoperative anemia in elective THA and TKA.…”
Section: Figuresupporting
confidence: 88%
See 1 more Smart Citation
“…Our analysis demonstrates that within our machine‐learning risk‐model, the preoperative Hb threshold for an increased risk of prolonged length of stay or readmissions due to medical issues was 14.8 g/dL in both men and women. This is similar as a recent study in about 7000 THA and TKAs (only 25% within fast‐track/ERAS programs) which reported fewer postoperative complications with a Hb >14.0 g/dL 7 . Thus, the results of both studies support removing the gender‐specific Hb criteria for preoperative anemia in elective THA and TKA.…”
Section: Figuresupporting
confidence: 88%
“…This is similar as a recent study in about 7000 THA and TKAs (only 25% within fast-track/ERAS programs) which reported fewer postoperative complications with a Hb >14.0 g/dL. 7 Thus, the results of both studies support removing the gender-specific Hb criteria for preoperative anemia in elective THA and TKA. Furthermore, the influence of a preoperative Hb level <14.8 g/dL appeared largely age-independent, supporting that the gender differences should be removed regardless of patient age.…”
supporting
confidence: 88%
“…Blood management is an important part of ERAS [ 16 ], higher preoperative hemoglobin level in a certain range is related to the reduction of complications after TKA, Cai and his group found that the LOS decreased with increased hemoglobin values when Preoperative Hemoglobin was beyond 140 g/L [ 27 ]. Further studies show that preoperative hemoglobin ≥ 140 g/L is associated with a lower risk of postoperative complications in patients undergoing primary TKA [ 28 ]. Li and his co-worker found that preoperative anemic patients had higher rates of complications, extended LOS, and mortalities [ 29 ], and preoperative anemia also affected the postoperative blood transfusion rate [ 30 ].…”
Section: Discussionmentioning
confidence: 99%